Simply a question of access? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Poverty is an insult. Poverty stinks. It demeans, dehumanises, destroys the body and the mind if not the soul. It is the deadliest form of violence, Mahatma Gandhi asserted earlier this century. Worst of all, poverty persists and outlives even the...